Randomised placebo-controlled trial of combination ACE inhibitor and beta-blocker therapy to prevent cardiomyopathy in children with Duchenne muscular dystrophy? (DMD Heart Protection Study): a protocol study. Issue 12 (19th December 2018) - Bourke, John P; Watson, Gillian; Muntoni, Francesco; Spinty, Stefan; Roper, Helen; Guglieri, Michela; Speed, Chris; McColl, Elaine; Chikermane, Ashish; Jayawant, Sandeep; Adwani, Satish; Willis, Tracey; et al.
Abstract : Introduction: Although cardiologists were 'late-comers' to the multidisciplinary team—contributing to the complex care of patients with Duchenne muscular dystrophy (DMD), they now recognise the importance of systematic cardiac surveillance and timely therapy to prolonged survival in patients with DMD. Empirical deployment of cardioactive medications has already improved outcomes, but the evidence base for clinical decision making is weak. Fundamental questions remain as to whether prophylactic therapy is justified and convincingly superior to prompt deployment of the same therapies once left ventricular (LV) dysfunction is detected. Even if it were, at what age should therapy be introduced and with what specific drugs? Methods and analysis: We are conducting a multicentre, parallel group, randomised, placebo-controlled study of combination therapy with an ACE inhibitor (perindopril) and a beta-blocker (bisoprolol) in boys with DMD aged 5–13 years, with normal LV function by echocardiographic criteria at the time of recruitment. Boys are being followed-up for a minimum of 3 years and a maximum of 5 years and undergo repeat assessments of LV function, heart rate and ECG, forced expiratory volume in the 1 s and forced vital capacity, adverse event reporting and quality of life at 6 monthly intervals. The primary outcome is change in LV function between active and placebo-treated participants over the course of the study. Ethics and dissemination: The study was approved by 'NRES Committee East Midlands – Derby'. The results will be disseminated through manuscript publications, an international workshop and presentations to scientific meetings and parent forums. Translational aspects: The study seeks to establish the evidence for prophylactic heart therapies for children with DMD, define the optimum age for their introduction and identify any safety concerns. Article summary: The protocol describes the design of an ongoing multicentre, double-blind, randomised placebo-controlled study to establish the evidence for the use of prophylactic heart therapies in children with DMD, define the optimum age for their introduction and identify any safety concerns. Trial registration numbers: EudraCT2007-005932-10 and ISRCTN50395346 ; Pre-results.